Detection of Histoplasma Capsulatum in Domestic Chicken Droppings in Olenguruone, Nakuru County - Kipyegon, Kemoi Edson; Musyoki, Stanslaus Kiilu; Kariuki, Stephen Mwaura (European Scientific Journal, ESJ, 2017)
Histoplasmosis is a serious community acquired fungal infection among immunocompetent and immunocompromised individuals. Chicken droppings were evaluated for the presence of Histoplasma capsulatum, by culturing in Blood agar, SABHI and SDA agar at 25Â°C and 37Â°C. Exoantigen were used for confirmation. Two Histoplasma capsulatum were isolated in this study. The study found that Chicken droppings harbor Histoplasma species.